2017
DOI: 10.1155/2017/9765843
|View full text |Cite
|
Sign up to set email alerts
|

Use of Limiting Dilution Method for Isolation of Nucleus Pulposus Mesenchymal Stem/Progenitor Cells and Effects of Plating Density on Biological Characteristics and Plasticity

Abstract: Objectives To evaluate the effects of the limiting dilution method and plating density in rat nucleus pulposus mesenchymal stem/progenitor cells (NPMSCs). Materials and Methods Nucleus pulposus tissues were isolated from 12-week-old male Sprague-Dawley rats and NPMSCs were isolated using limiting dilution method. Cells were then classified into 3 groups according to plating density. Cell morphologies were observed, and colony-forming units, migration abilities, proliferative capacities, cell cycle percentages,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In the past decade, supplementation with exogenous mesenchymal stem cells (MSCs), such as MSCs derived from bone marrow and adipose tissue, has shown positive outcomes for the repair of IVD degeneration [ 4 ]. And in recent years, evidence has been found that endogenous nucleus pulposus-derived mesenchymal stem cells (NPMSCs) exist naturally in the IVDs [ 5 7 ]. As a novel approach to repairing disc degeneration, application of endogenous NPMSCs has shown exciting prospect and attracted increasing attention [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, supplementation with exogenous mesenchymal stem cells (MSCs), such as MSCs derived from bone marrow and adipose tissue, has shown positive outcomes for the repair of IVD degeneration [ 4 ]. And in recent years, evidence has been found that endogenous nucleus pulposus-derived mesenchymal stem cells (NPMSCs) exist naturally in the IVDs [ 5 7 ]. As a novel approach to repairing disc degeneration, application of endogenous NPMSCs has shown exciting prospect and attracted increasing attention [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al cultured NPMSCs of rats in vitro and induced differentiation, and found that NPMSCs could express stem cell genes, such as SOX2, Oct4 and Nanog [15]. Hui Zhang et al compared rat NPMSCs and bone marrow mesenchymal stem cells by in vitro culture, and found that both can differentiate into bone, cartilage and fat, and can express stem cell genes Nanog, oct-4 and sox-2, with no obvious difference [16].…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al cultured NPMSCs of rats in vitro and induced differentiation, and found that NPMSCs could express stem cell genes, such as SOX2, Oct4 and Nanog [15]. Hui Zhang et al compared rat NPMSCs and bone marrow MSCs by in vitro culture, and observed that both of them could differentiate into bone, cartilage and fat, and could express stem cell genes Nanog, Oct-4 and SOX-2, with no obvious difference [16].…”
Section: Discussionmentioning
confidence: 99%